XAS studies of pressure-induced structural and electronic transformations in α-FeOOH. (29th May 2019) - Trcera, N; Layek, S; Shulman, M; Polian, A; Irifune, T; Itié, J-P; Rozenberg, G Kh
Abstract: Structural and electronic transformation taking place in α -FeOOH goethite have been studied by Fe K -edge x-ray absorption spectroscopy at pressures up to 50 GPa. These studies have shown the symmetrization of FeO6 octahedra coinciding with the Fe 3+ high to low spin transition at pressure above 45 GPa. Our data are in excellent agreement with the results of recent single crystal XRD and Mössbauer spectroscopy studies (Xu et al 2013 Phys. Rev. Lett .111 175501), supporting the H-bonds symmetrization in iron oxyhydroxide, resulting from the Fe 3+ high-to-low spin crossover at above 45 GPa. Our study shows an applicability of the x-ray absorption spectroscopy in a further study of the H-bonds symmetrization phenomenon.